Green, Resilient and Inclusive Development through Leadership: Pathways for Social Enterprises in Nepal - Paudel , Vishal (Journal of Kathmandu BernHardt College, 2025)
This study examines the mediating role of leadership in the relationship between Green, Resilient, and Inclusive Development (GRID) and Sustainable Business Performance (SBP) within the context of social enterprises in Nepal. Using a quantitative cross-sectional survey design, data were collected from 399 respondents representing social enterprises, non-governmental organizations, and development institutions. Constructs were measured using structured, Likert-type questionnaires validated through reliability and factor analysis. Analytical methods included descriptive statistics, correlations, regression, and partial least squares structural equation modeling (PLS-SEM). Results reveal that leadership traits (adaptability, collaboration, and exploration) play a significant mediating role between GRID dimensions and SBP outcomes. Leadership enhances team innovation, strengthens economic and social sustainability, and supports the operationalization of GRID in enterprise performance. The study confirms the applicability of Dynamic Capabilities Theory and Ambidextrous Leadership Theory in explaining leadership’s mediating effects. Findings provide both theoretical contributions and practical implications for promoting sustainability-driven leadership practices in developing country contexts.